Architecture of microtubule cytoskeleton in the hindgut cells of Porcellio scaber - Urban Bogataj; Polona Mrak; Jasna Štrus; Nada Žnidaršič (ZooKeys)
The distribution and orientation of microtubules were investigated in cells of distinct shapes from different hindgut regions of adult Porcellio scaber Latreille, 1804 and during hindgut morphogenesis in late embryonic and early postembryonic development. All hindgut cells of adult P. scaber contain abundant apico-basal microtubules organized in extensive bundles, but the architecture of bundles is specific for distinct cells. In the anterior chamber the architecture of microtubule bundles closely coincides with different shapes of the cells in this hindgut region and are most prominent in hindgut cells associated with extensive muscles. The shape of cells that form the typhlosole and typhlosole channels is particularly complex. In the papillate region the microtubule bundles protrude between the infoldings of apical plasma membrane and the mitochondria are closely aligned along the microtubules, thus the microtubule bundles in the papillate region are likely involved in the stabilization of the apical labyrinth and positioning of mitochondria. During hindgut morphogenesis the apico-basal microtubule bundles are established relatively late, mainly during early postembryonic development. Morphogenesis of the typhlosole is characterized by coinciding changes in cell shape and microtubule arrangement.